Purchase Behavior of Millennial Female Generation (Gen-Z) on Halal Cosmetic Products in Semarang - Arif Afendi; Farida Indriani (Universitas Mercu Buana, 2022)
Objectives: The objective of this research is to analyze the impact of religious beliefs on attitude toward halal awareness and purchasing decisions behavior of halal cosmetic products. This was a quantitative study utilizing multiple linear regression. Methodology: The data for this study was obtained from primary interviews with 160 respondents in Semarang who use halal cosmetic products. The sampling technique was random sampling. Data is processed using SEM-PLS programs. Finding: The research shows a positive and significant effect of religious belief on attitude toward halal awareness. Religious belief has a positive and significant effect on purchasing decision behavior, and attitude toward halal awareness has a positive and significant effect on purchasing decision behavior. Religious belief has a positive and significant effect on purchasing decisions mediated by attitude toward halal awareness. Conclusion: The conclusion of this study shows that the level of a customer's religious beliefs will improve purchasing decision behavior. Furthermore, the higher the level of halal awareness a customer has, the more purchasing decision behavior will increase.